Experimental evolution of resistance to artemisinin combination therapy results in amplification of the mdr1 gene in a rodent malaria parasite - Rodrigues, Louise A.; Henriques, Gisela; Borges, Sofia T.; Hunt, Paul; Sanchez, Cecilia P.; Martinelli, Axel; Cravo, Pedro (PLOS ONE, 2010)
Background Lacking suitable alternatives, the control of malaria increasingly depends upon Artemisinin Combination Treatments (ACT): resistance to these drugs would therefore be disastrous. For ACTs, the biology of resistance to the individual components has been investigated, but experimentally induced resistance to component drugs in combination has not been generated. Methodology/Principal Findings We have used the rodent malaria parasite Plasmodium chabaudi to select in vivo resistance to the artesunate (ATN) + mefloquine (MF) version of ACT, through prolonged exposure of parasites to both drugs over many generations. The selection procedure was carried out over twenty-seven consecutive sub-inoculations under increasing ATN + MF doses, after which a genetically stable resistant parasite, AS-ATNMF1, was cloned. AS-ATNMF1 showed increased resistance to ATN + MF treatment and to artesunate or mefloquine administered separately. Investigation of candidate genes revealed an mdr1 duplication in the resistant parasites and increased levels of mdr1 transcripts and protein. There were no point mutations in the atpase6 or ubp1genes. Conclusion Resistance to ACTs may evolve even when the two drugs within the combination are taken simultaneously and amplification of the mdr1 gene may contribute to this phenotype. However, we propose that other gene(s), as yet unidentified, are likely to be involved.